National launch of Climate Smart Governance (CSG) Dashboard and strengthening Multi-scale Polycentric Governance (MPG) Tool in Kenya - Alahacoon, Niranga; Amarasinghe, Upali; Amarnath, Giriraj (International Water Management Institute (IWMI), 2024)
Kenya’s climate, influenced by topography, varies from tropical along the coast to semi-arid and arid in the interior. The country experiences bimodal rainfall patterns, with long rains from March to May and short rains from October to December. However, climate change has disrupted these patterns, increasing the prevalence of extreme weather events such as droughts, floods, landslides, and cyclones. Rainfall variability has intensified, with wetter northern regions contrasting sharply with drier southern areas. This heightened variability and Kenya's reliance on rainfed agriculture underscore its vulnerability to climate hazards, which have far-reaching impacts on its economy, environment, and population.